DAMPAK HUTANG PIUTANG DALAM TRADISI TONJOKAN DAN BINGGELAN ACARA HAJATAN MENURUT PERSPEKTIF EKONOMI ISLAM - Muharir Muharir (FEBI Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Accounts payable is a muamalah transaction that is often carried out by a person, group of people or corporate entities, in today's digital era many people make these transactions to fulfill their needs or just fulfill their desires. Economic factors and social status are often the basis for someone to carry out debt transactions. Tonjokan and binggelan traditions have their own terms and meanings. Tonjokan means flattery from sohibul hajat in the form of rice and side dishes with the intention of inviting people to come to the celebration party later by bringing cash wrapped in an envelope, the size of the envelope, according to the money previously given. by sohibul hajat when he arrives at the party who is invited or is called a debt, while binggelan is a donation in the form of goods or money that is deposited with sohibul hajat according to what is needed when the celebration takes place from the jiron community, neighbors, relatives and family, in the hope that in the future it will help which gives binggelan alternately. In writing this paper, the author also uses a qualitative method with a social and economic approach with the results of the discussion of the impact that is generated there is also a positive side and is still in accordance with the provisions of sharia economics in muamalah transactions, namely to help and strengthen the relationship between human beings. Behind the tradition of tonjokan and binggelan celebrations there are many positive values ​​that can be taken in it and even then in accordance with the mandate of the third Pancasila principle, namely the unity of Indonesia and the motto of the Indonesian State, namely Bhineka Tunggal Ika (although they are different but still one).